Association of glomerular filtration rate with high-sensitivity cardiac troponin T in a community-based population study in Beijing. (12th October 2011) - Fan, Wang; Ping, Ye; Leiming, Luo; Ruyi, Xu; Yongyi, Bai; Hongmei, Wu
Abstract : Objective: The reduced level of glomerular filtration rate (GFR) is an independent risk factor for cardiovascular disease (CVD) mortality and persistently elevated cardiac biomarkers are frequently observed in patients with end-stage renal disease. In general population, however, the clinical use of the serum levels of cardiac biomarkers has limitations because of the low sensitivity of the assay system. Recently, a highly sensitive cTnT (hs-cTnT) assay has become commercially available. In the present study, the authors investigated the cTnT level using highly sensitive commercial assay, evaluated the association of eGFR with hs-cTnT in community-based population in Beijing. Methods: The serum hs-cTnT levels were measured in a community-based population (n=1497; 48.1% men; aged ≥45 years) living in Pingguoyuan area of the Shijingshan district, a metropolitan area in Beijing, China. The lower detection limit of the hs-cTnT assay used in the present study was 3 pg/ml. eGFR was evaluated by the Chinese modified Modification of Diet in Renal Disease equation. Anthropometry, blood pressure, fasting plasma glucose (FPG), serum total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), uric acid (UA) and NT-proBNP were measured. Pearson's correlation and a multivariate logistic regression modelling were used to used to establish the relationship between eGFR value and detectable hs-cTnT value. Results: With the highly sensitive assay, detectable hsTnT levels were seen (> 3 pg/ml) in 798 subjects (54.9%) and concentrations of cardiac troponin T were at or above 13.3 pg/ml in 178 patients (11.9%). The level of hs-cTnT was increased in patients with hypertension, diabetes, coronary artery disease and/or renal insufficiency. The result of Pearson correlation showed that eGFR was associated with hs-cTnT (r=−0.14, p<0.001). After adjustment for other risk factors, the results of multivariate logistic regression analysis showed eGFR were independently inversely associated with hs-cTnT (adjusted odds ratio, 0.57; 95% CI, 0.36 to 0.77; p<0.001) in this study group. Conclusion: The present study showed that after adjusting for multiple potential confounders, eGFR were significantly associated with cardiac troponin T concentrations as measured with a highly sensitive assay in the community-based subjects.